Circular RNA hsa_circ_0000467 Promotes the Development of Gastric Cancer by Competitively Binding to MicroRNA miR-326-3p. (6th February 2020) - Mo, Wei Lie; Jiang, Jing Ting; Zhang, Luo; Lu, Qi Cheng; Li, Jing; Gu, Wei Dong; Cheng, Yun; Wang, Hai Tao
Abstract : Circular RNAs are a class of endogenous noncoding RNAs that play an important role in gene regulation. These RNAs are involved in the development and progression of various cancers, but their roles in gastric cancer have not yet been thoroughly elucidated. This study showed that hsa_circ_0000467 expression was higher in gastric cancer tissues than in corresponding adjacent tissues (P < 0.050 ) and that hsa_circ_0000467 expression levels were correlated with gastric cancer histological grade (P < 0.050 ). In addition, hsa_circ_0000467 was remarkably upregulated in gastric cancer cell lines (P < 0.001 ). Cell function experiments indicated that hsa_circ_0000467 downregulation decreased the proliferation and invasion ability of BGC-823 and SGC-7901 cells and the number of cells entering the G2/M phase. A direct binding interaction was detected between hsa_circ_0000467 and miR-326-3p by dual-luciferase reporter assays. In addition, the results showed that inhibition of miR-326-3p reversed the decreases in the proliferation and invasion of BGC-823 and SGC-7901 cells caused by hsa_circ_0000647 downregulation. Inhibition of miR-326-3p also decreased the number of cells entering the G2/M phase and the expression of cyclin D1. In conclusion, hsa_circ_0000467 plays a regulatory role in the development and progression of gastric cancer by regulating miR-326-3p, and this circRNA may be a potential diagnostic marker and therapeutic target of gastric cancer.